Rhizobacterial consortium mediated aroma and yield enhancement in basmati and non-basmati rice ( Oryza sativa L.) - Dhondge, Harshal V.; Pable, Anupama A.; Barvkar, Vitthal T.; Dastager, Syed G.; Nadaf, Altafhusain B. (Journal of Biotechnology, 2021)
Basmati and non-basmati rice varieties are commercially important. Aromatic rice varieties are low yielding and recently depletion in aroma is observed due to the shift towards modern agriculture. Therefore, it is necessary to restore the aroma and increase the yield through sustainable agriculture. The use of microbial bioinoculants is one of the promising ways to achieve these targets. With these objectives, rhizospheric bacterial strains Enterobacter hormaechei (AM122) and Lysinibacillus xylanilyticus (DB25) having the property of synthesizing 2acetyl-1-pyrroline (2AP) were isolated from the rhizosphere of two aromatic rice varieties, Ambemohar-157 and Dehradun Basmati respectively and their effect on plant growth, aroma and yield enhancement under mono-inoculation and consortium conditions was analyzed. The bacterial inoculum in consortium resulted in significant improvement in vegetative growth, yield and 2AP content over mono inoculation and control. The study highlights the potential of E. hormaechei and L. xylanilyticus in plant growth, yield and aroma enhancement in basmati and non-basmati rice varieties. These strains can be taken up further for developing a commercial bioformulation.
Keywords: 2-Acetyl-1-pyrroline; Basmati rice; Non-basmati rice; plant growth promotion; Rhizosphere; yield

Role of ions and their transporters in combating salt stress in Pandanus odorifer (Forssk.) Kuntze - Rashmi, Deo; Ansari, Waquar A.; Kadoo, Narendra Y.; Barvkar, Vitthal T.; Deshmukh, Rupesh; Nadaf, Altafhusain B. (Acta Physiologiae Plantarum, 2023)
Soil salinity is a major environmental constraint causing huge losses in crop production. Pandanus odorifer (Forssk.) Kuntze is an aromatic monocot plant species belonging to the family Pandanaceae, which grows naturally on the saline soils along the coasts of Asia, Southeast Asia, and Polynesia. The plants are dioecious and highly fertile, and the consistent saline sprays, strong winds, and severe soil salinity hardly affect their growth and fertility. Hence, understanding the mechanism of high salinity tolerance in P. odorifer could provide major advances in overcoming salinity stress in crop plants. In the present study, we analyzed control (0 M NaCl) and treated (1 M NaCl treatment for 3 weeks) plants of P. odorifer to understand the role of ion distribution, ion transport, and related mechanisms under salt stress. Using a combination of ionomics and transcriptomics approaches, we identified the molecular mechanisms contributing to the high salinity stress in P. odorifer. Under NaCl stress, there was a significant increase in Na, Cl, and other ions in leaves, while the concentrations of Si, Fe, Ni, and Ti decreased. Similarly, in roots, the levels of Na, Mg, Cd, and Cr were significantly high, while the levels of other ions decreased. Most of the genes related to ion transport and homeostasis, such as NHX1, CLC-C, SOS1, HAK, and ABC transporters, were upregulated in 1 M NaCl stress conditions. This study revealed that vacuolar sequestration of Na+ and the distribution of ions in the roots and shoots play significant roles in the salt-stress tolerance mechanism of P. odorifer.
Keywords: Ion transport; Ionomics; Pandanus; Salinity tolerance; Transcriptomics; Vacuolar sequestration